SOSIALISASI PEMAHAMAN MASYARAKAT TERHADAP KEBIJAKAN PUBLIK DI KAMPUNG PAWEKAMA DISTRIK WALESI KABUPATEN JAYAWIJAYA - Tukijan, Tukijan; Tambunan, Ayu Anggraini; Amir, Aswad (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
In Kampung Pawekama, Walesi District, Jayawijaya Regency, the community upholds the legacy of socio-cultural values through strong kinship relations. Nevertheless, within the context of development, they advocate for pro-people public policies to achieve prosperity. Unfortunately, it is regrettable that the community's understanding of various public service programs aimed at enhancing welfare remains inadequate. The objective of this Community Service Program (PKM) is to enhance the comprehensive understanding of how the Kampung Pawekama community perceives public policies aimed at village welfare. Utilizing qualitative methods and purposive informant selection, this research aims to gather relevant data and information. The findings indicate that the Kampung Pawekama community still lacks a complete understanding and awareness of various public policies designed to enhance their welfare. Additionally, it was found that public policy socialization faces challenges due to internal factors within government units and a lack of community awareness regarding welfare improvement programs.